Teorier om dufortællinger: En blindgyde? - Reitan, Rolf (K&K - Kultur og Klasse, 2011)
THEORIZING SECOND-PERSON NARRATIVES: A BACKWATER PROJECT? | In this paper Rolf Reitan proposes a closer look at three very different perspectives on second person narrative: Brian Richardson, Irene Kacandes, and Monika Fludernik have been classical references for some time, but they have never, according to Reitan, been seriously discussed. The paper begins by examining Kacandes’ intriguing concept of ‘radical narrative apostrophe’, and then discusses the three authors’ very different typological proposals. Borrowing Richardson’s idea of a Standard Form of second person narration, it returns to Butor’s La Modification to investigate the question of address (a pivotal question in Fludernik’s articles), which then leads to a strict definition of a prototypical “genre” of Standard Form narratives. Passing through conceptual landscapes of fiction, apostrophe, and postmodernism, some tricky questions concerning selfaddress, and some of Margolin’s analytic formulas, are considered. At last, by way of proposing a much needed subdivision of the Standard Form, Reitan discusses the strange narrating voice in La modification: not a narratorial voice, but a readerly voice created in the author’s writing.